Hygiene Analysis of Food Handlers at Malahayati Islamic Hospital - Reni Agustina Harahap; Nadita Kirani; Hazanah Hartasya; Amenda Sabarita Br Sitepu; Indah Khairunnisa Nst; Devi Irmayani; Nanda Putri Purba; Sabrina Renanda; Putri Syahrani; Hamni Kholilah Nst; Annisa UI Husnah (Universitas Malahayati, 2024)
ABSTRACT Hospital food management is a series of activities starting from menu planning to distributing food to patients. Providing food in hospitals is an activity that is under the responsibility of the Nutrition Installation. In carrying out his duties, a food handler in a nutrition installation must always maintain personal hygiene so that the cleanliness and quality of the food served to patients is maintained. This study aims to determine the description of the hygiene of food handlers at the Malahayati Islamic Hospital. The method used in this research is qualitative with a description method. The informants in this research were 10 people, cooks and waiters at Malahayati Islamic Hospital. Based on the results obtained, it was found that the implementation of food handler hygiene at RSI Malahayati Medan was included in the good category, with a percentage of 93%. However, in practice, there are still food handlers who do not use PPE (Personal Protective Equipment) when serving food. The implementation of food handler hygiene at the Malahayati Islamic Hospital does not fully meet the standards of the Regulation of the Minister of Health of the Republic of Indonesia Number 1096/Menkes/Per/VI/2011. Keywords: Food Handler, Hospital Food Management ,Hygiene